Electronic Security System for Agricultural Field - Rai, A. K.; Khare, P. K.; Mor , Prashant (Novel Perspectives of Engineering Research Vol. 10, 2022)
Today, agricultural field security is extremely vital. Agricultural field threats can originate from a variety of places. Producers must be aware of the possibility of intentional crop loss or contamination. If utilised inappropriately or indiscriminately, safe drugs can be used to create unsafe or harmful mixtures. Chemicals and physical injury are examples of this. The farmer must protect the field from all acts of purposeful devastation. In order to protect the crop in the field, a method has been developed. The devised method will aid in identifying and, in many cases, thwarting intrusions into crop fields. It's a fence system that not only detects when rouge animals enter the field, but also drives them out.